Pemberian Hiperoksigenasi Pada Proses Open Suction Terhadap Perubahan Saturasi Oksigen di ICU - Marleza Oktavia; Vincencius Surani; Dheni Koerniawan (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Critical patients are patients who are in the Intensive Care Unit (ICU) because they have lost consciousness, one of the reasons being respiratory failure. In patients with respiratory failure who have an ETT installed and connected to a mechanical ventilation device, there can be a buildup of phlegm/secretions in the bronchi and alveoli area so that the patient's airway can be disrupted, so an effective intervention is suction. In the suction process, hyperoxygenation can be carried out first to maintain oxygen saturation levels within normal limits. To overcome airway clearance in patients who experience ineffective airway clearance nursing problems and describe nursing care. The method used in this research is a case study that describes the nursing care of a patient who had an Endotraceal Tube (ETT) installed who experienced ineffective airway clearance. The results of the assessment of the three patients experienced problems with ineffective airway clearance and hyperoxygenation was carried out in the open suction process to maintain oxygen saturation values ??within normal limits. The results obtained showed changes in oxygen saturation before and after the open suction procedure. It is hoped that the provision of hyperoxygenation intervention in the open suction process can be carried out according to the SOP so that complications do not occur.